Pengaruh Dosis Tepung Biji Sirsak (Annona muricata L.) Terhadap Mortalitas Hama Gudang (Sitophilus oryzae L) Pada Beras Hitam (Oryza sativa L) - Indra Indra; R. Budiasih; Endeh Masnenah; Elly Roosma Ria (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
Sitophilus oryzae L is a beetle pest that attacks black rice grains during storage, causing the rice to become damaged and reducing the quantity and quality of black rice. One of the efforts to control beetle pests in black rice storage warehouses is the use of soursop seed flour. The aim of this research to study and obtain the dosage of soursop seed flour which gives the best effect on mortality, the amount of imago, percentage of damage and percentage of weight loss of black rice (Oryza sativa L). The experiment was conducted at the Faculty Of Agriculture of Winaya Mukti, Tanjungsari, Sumedang, in July to September 2020. The experiment used a Completely Randomized Design (CRD) with six treatments and four replication, consist of : A = 0 g/100 g black rice seeds, B = 2 g/100 g black rice seeds, C = 4 g/100 g black rice seeds, D = 6 g/100 g black rice seeds, E = 8 g/100 g black rice seeds and F = 10 g/100 g black rice seeds. The results showed that soursop seed flour had a good effect on mortality and the amount of S. oryzae L. imago, percentage of damage, and percentage of weight loss of black rice (O. sativa L).The dose of soursop seed flour 2 g/100 g black rice, effectively increased mortality, suppressed the amount of imago S. oryzae L. , percentage of damage and percentage of weight loss of black rice (O. sativa L)